Relevansi Bab Nikah dalam Kitab Hasyiyah Qalyubi Wa Umairah dengan Konteks Kontemporer: Perspektif Pembelajaran di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: The Relevance of the Marriage Chapter in the Hasyiyah Book Qalyubi Wa Umairah to the Contemporary Context: Learning Perspectives at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Bintang Maharani Hidayat Putri; Retno Wulandari; Muhammad Rizqi Al-Fajri (DIRASAH: Jurnal Kajian Islam, 2025)
This research examines the relevance of the Chapter of Marriage (Bab Nikah) in Hasyiyah Qalyubi wa Umairah within a contemporary context through the lens of learning practices at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta. The study stems from the importance of understanding classical fiqh teachings derived from traditional Islamic scholarship (kitab kuning) as an intellectual heritage, while also evaluating their compatibility with the social dynamics and modern marriage laws in Indonesia. The objective of this research is to analyze how students’ understanding of the Chapter of Marriage is contextualized in the educational practices of the pesantren, as well as to assess the extent to which the classical fiqh values remain relevant to the current social and legal realities of society. This study employs a qualitative-descriptive approach, using data collection techniques such as interviews, observations, and literature studies on both the classical text and students’ learning activities. The findings indicate that the pesantren maintains traditional teaching methods (bandongan and sorogan), yet adapts them through contextual discussions on modern marriage issues such as marriage registration, women’s rights, and the role of guardians (wali) within the national legal system. In conclusion, the Chapter of Marriage in Hasyiyah Qalyubi wa Umairah retains a high degree of relevance when taught through a critical and contextual approach that integrates classical texts with contemporary needs, thereby strengthening the pesantren’s role as both a preserver of tradition and an agent of socio-religious transformation.